CARACTERIZAÇÃO E AVALIAÇÃO BIOLÓGICA DA FRAÇÃO ACETATO DE ETILA DE Harpagophytum procumbens - Lima, Valtieri Bortoluzzi de (2020)
Neuropsychiatric diseases arouse interest in researches due to the complexity of understanding its pathophysiology, diagnoses and treatments. Particularly important, schizophrenia contemplates multiple hypotheses, which are associated with its development, including hypotheses such as dopaminergic, neuroinflammation and oxidative stress. The treatment is currently based on antipsychotics. Although they present good clinical efficiency, they end up bringing several negative effects. In this regard, herbal medicines have been researched as a therapeutic resource for many diseases. Harpagophytum procumbens, a plant of African origin, demonstrates benefits due to its anti-inflammatory effect, its main biological property well elucidated in the literature, besides the neuroprotective and antioxidant effects presented in the researches. Therefore, the aim of this study was to verify the effect of pretreatment with a fraction ethyl acetate from Harpagophytum procumbens on the animal model of amphetamine-induced psychosis through parameters such as locomotive and exploratory activity, stereotyped movements and working memory, as well as parameters such as oxidative stress through levels of thiol groups and production of reactive oxygen species. In the in vitro model, cell activation and proliferation were observed over the pretreatment with the ethyl acetate fraction of Harpagophytum procumbens in microglia, as well as parameters of oxidative stress in vitro and an interference in the cell cycle. Our results demonstrate that the ethyl acetate fraction of Harpagophytum procumbens prevents behavioral changes in mice induced by amphetamine, exhibits antioxidant activity in vivo and in vitro and demonstrates antiproliferative activity in microglia, modulating the cell cycle.